Evaluation of Poor Area Understanding Under Cigarettes in Lebak District - Nurhasanah, Nurhasanah; Ayuningtyas, Dumilah (Journal of Indonesian Health Policy and Administration, 2017)
Regional Regulation of Lebak District No.17 of 2006 on the Implementation of Order, Hygiene and Beauty is a derivative form of Government Regulation No.109 Year 2012 About Security of Materials Containing Addictive Substance in the form of Tobacco Products for Health. One of the mandate in the regulation is the establishment of Non Smoking Area (KTR) as an effort to protect the public against the health risks caused by the environment contaminated with tobacco smoke. Because health hazards caused by cigarettes not only affect the smokers but also passive smokers. WHO even mentioned that less than 6 million people died from smoking and exposure to cigarette smoke. The purpose of this research is to evaluate the implementation of KTR policy in Lebak District. This research uses Triangulation mix methode, data collection is done with qualitative and quantitative approach. The results obtained only a small percentage of people who adhered to the KTR policy (28%), the community behaved positively for smoking (58%) and high knowledge of cigarette and KTR hazards (58%) and no relationship between behavior and knowledge (p value = 0.075). Implementation of the policy of No Smoking Area has not been effective because there is still a difference between implementation and guidance in the use of Excise Revenue Sharing Fund from the Ministry of Health. Local governments have not been responsive to KTR policy with the issuance of Local Regulations on Non-Cigarette Regions, the formation of supervisory teams and socialization of local regulations. Recommendations that can be submitted are the issuance of Regional Regulations on Non-Smoking Areas, and the perception agreement of the use of Tobacco Revenue Sharing Funds on policy makers.